Walking stability during cell phone use in healthy adults - Kao, Pei-Chun; Higginson, Christopher I.; Seymour, Kelly; Kamerdze, Morgan; Higginson, Jill S. (Gait & posture, 2015)
•We examined walking stability during cell phone use and classic cognitive tasks.•Healthy subjects’ walking stability was not compromised by the dual task.•Subjects increased step width and reduced lower-limb joint variability during dual-tasking.•A dual task taxing physical alteration or visual attention causes greater gait modification.•Minimizing physical alteration or visual distraction associated with cell phone use may help reduce falls. The number of falls and/or accidental injuries associated with cellular phone use during walking is growing rapidly. Understanding the effects of concurrent cell phone use on human gait may help develop safety guidelines for pedestrians. It was shown previously that older adults had more pronounced dual-task interferences than younger adults when concurrent cognitive task required visual information processing. Thus, cell phone use might have greater impact on walking stability in older than in younger adults. This study examined gait stability and variability during a cell phone dialing task (phone) and two classic cognitive tasks, the Paced Auditory Serial Addition Test (PASAT) and Symbol Digit Modalities Test (SDMT). Nine older and seven younger healthy adults walked on a treadmill at four different conditions: walking only, PASAT, phone, and SDMT. We computed short-term local divergence exponent (LDE) of the trunk motion (local stability), dynamic margins of stability (MOS), step spatiotemporal measures, and kinematic variability. Older and younger adults had similar values of short-term LDE during all conditions, indicating that local stability was not affected by the dual-task. Compared to walking only, older and younger adults walked with significantly greater average mediolateral MOS during phone and SDMT conditions but significantly less ankle angle variability during all dual-tasks and less knee angle variability during PASAT. The current findings demonstrate that healthy adults may try to control foot placement and joint kinematics during cell phone use or another cognitive task with a visual component to ensure sufficient dynamic margins of stability and maintain local stability.